6,6’-DIMETHOXY-4,4’-DIHYDROXY-3’,2’-FURANO-ISOFLAVANE, A NEW COMPOUND FROM Melochia umbellata (Houtt.) Stapf var. Degrabrata K. (Paliasa) - Erwin Erwin; Alfian Noor; Nunuk Hariani Soekamto; Tjodi Harlim (Universitas Gadjah Mada, 2010)
Using data from UV, IR, 1H-NMR, 13C-NMR, dan NMR-2D analysis, a compound of 6,6'-dimethoxy-4,4'-dihydroxy-3',2'-furano-isoflavane (1) was successfully isolated from chloroform fraction of heartwood in Melochia umbellata (Houtt.) Stapf var. Degrabarata K (Paliasa). Hitherto no report of such compound found in literature. The compound however has not shown a significant bioactivity according to either brine shrimp lethality test or evaluation of anti tumor activity against leukemia murine cell (P-388).